A refined numerical model for determining inflation-burst behavior of composite membrane structures. (January 2020) - Shi, Taibai; Hu, Jianhui; Chen, Wujun; Gao, Chengjun
Abstract: The airship structures made of multi-layer composite fabrics or membranes can offer the platform for earth observations, wireless communications and space research due to light weight and good mechanical performance. The structural safety and serviceability strongly depend on material properties and working conditions. Available studies are limited within service stress limits or are lack of suitable biaxial tensile constitutive models for understanding structural behavior. This paper thus focuses on a refined numerical model for determining inflation-burst behavior of composite airship structures considering new biaxial constitutive equations, novel failure criteria and manufacture factors. The differences between ideal and real forms of airship structures, e.g. volume difference, demonstrate the necessity for incorporating cutting-pattern effects in the initial numerical model. For structural analysis, stress distributions on real structural forms are different from those on ideal forms because of welding parts that can enhance local stiffness. The ultimate pressures are 56.7 kPa and 59.5 kPa for ideal and real structural forms. Structural breaking initiated at the maximum diameter of ideal structural forms propagates fast while welding parts can prevent breaking propagation for real structural forms. Therefore, the refined numerical model can reveal basic structural behavior and safety performance of airship structures in the inflation-burst processes. Highlights: The inflation-burst behavior of composite airship structures is assessed. A refined numerical model is established and solved with new programs. Biaxial constitutive, failure criteria and real form are considered in new programs. Stress characteristics on ideal and real forms are quantified and compared. Structural breaking for ideal forms propagates much faster than real forms.